Cycling and recycling : histories of sustainable practices - Oldenziel, Ruth, 1958-; Trischler, Helmuth (Environment in history, 2016)
Technology has long been an essential consideration in public discussions of the environment, with the focus overwhelmingly on creating new tools and techniques. In more recent years, however, activists, researchers, and policymakers have increasingly turned to mobilizing older technologies in their pursuit of sustainability. In fascinating case studies ranging from the Early Modern secondhand trade to utopian visions of human-powered vehicles, the contributions gathered here explore the historical fortunes of two such technologies--bicycling and waste recycling--tracing their development over time and providing valuable context for the policy successes and failures of today.